Leadership and Principal Motivation on Teacher Performance at Madrasah - Jamilus, Jamilus; Murtadlo, Ghulam; Pahmi, Pahmi; Indriani, Dewi; Jasiah, Jasiah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine the influence of leadership and principal motivation on teacher performance at Madrasah Tsanawiyah Thawalib, Tanjung Limau Pariangan, West Sumatra. This study uses a quantitative correlational approach that is commonly used to evaluate and detect the extent of a factor's variation on one or more other factors based on the correlation coefficient. This study involved 30 teachers. The results showed that leadership and motivation simultaneously affected teacher performance at Madrasah Tsanawiyah Thawalib with a significance value (sig) of 0.003. The better the leadership and the higher the motivation given by the head of the madrasah, it will improve teachers' performance in the madrasah. This study has implications for the importance of the leadership style displayed by the principal in improving the performance of existing personnel in the organization to achieve the desired goals.